Population monitoring and modelling of yellow‐shouldered parrot on Bonaire, Caribbean Netherlands. Issue 1 (8th October 2018) - Rivera‐Milán, Frank F.; Simal, Fernando; Bertuol, Paulo; Boomer, G. Scott
Abstract : Abundance estimates based on adequate survey design and count methodology are needed for population monitoring and modelling, and for assessing the results of conservation actions taken to boost or maintain population size at desired target levels. We monitored Bonaire's population of yellow‐shouldered parrot Amazona barbadensis rothschildi using systematic distance sampling surveys in 2009–2017, and developed a Bayesian state‐space logistic model to predict changes in abundance resulting from increased human‐induced mortality in 2018–2066. Survey‐based abundance estimates (mean ± bootstrapped SE) were 0.172 ± 0.020 parrots ha ‐1 and 2924 ± 340 parrots at a survey region covering 17 000 ha. Model‐based posterior distribution estimates (mean ± MCMC SD) of maximum population growth rate, maximum sustainable mortality rate, maximum sustainable mortality, population carrying capacity and equilibrium population size were 0.179 ± 0.129, 0.090 ± 0.064, 219 ± 135, 5623 ± 2043 and 2811 ± 1022 parrots. With low to moderate mortality rates (0.001– 0.100, 0.101–0.250), predicted population sizes (mean ± MCMC SD) were 2963 ± 668 and 2703 ± 1660 parrots in 2018, and 2754 ± 690 and 2297 ± 1301 parrots in 2066. With high mortality rates (0.251–0.500), predicted population sizes were 1780 ± 1160 parrots in 2018 and 26 ± 139 parrots in 2066. Because the relative importance and magnitude of human–parrot conflicts are unknown but may be unsustainable, we consider the parrot population vulnerable to the risk of extinction during the modelled time horizon. Therefore, we recommend long‐term monitoring and modelling for assessing changes in abundance and the results of conservation actions taken to keep the population above 2800 parrots in the survey region (i.e. population size N > 2.5% percentile of the posterior distribution of population carrying capacity K ).